Rigid, bivalent CTLA-4 binding to CD80 is required to disrupt the cis CD80/PD-L1 interaction - Maximillian A. Robinson; Alan Kennedy; Carolina T. Orozco; Hung-Chang Chen; Erin Waters; Dalisay Giovacchini; Kay Yeung; Lily Filer; Claudia Hinze; Christopher Lloyd; Simon J. Dovedi; David M. Sansom (Cell Reports, 2024)
Summary: The CTLA-4 and PD-1 checkpoints control immune responses and are key targets in immunotherapy. Both pathways are connected via a cis interaction between CD80 and PD-L1, the ligands for CTLA-4 and PD-1, respectively. This cis interaction prevents PD-1-PD-L1 binding but is reversed by CTLA-4 trans-endocytosis of CD80. However, how CTLA-4 selectively removes CD80, but not PD-L1, is unclear. Here, we show CTLA-4-CD80 interactions are unimpeded by PD-L1 and that CTLA-4 binding with CD80 does not displace PD-L1 per se. Rather, both rigidity and bivalency of CTLA-4 molecules are required to orientate CD80 such that PD-L1 interactions are no longer permissible. Moreover, soluble CTLA-4 released PD-L1 only at specific expression levels of CD80 and PD-L1, whereas CTLA-4 trans-endocytosis released PD-L1 in all conditions. These data show that PD-L1 release from CD80 is driven by orientation and bivalent cross-linking of membrane proteins and that trans-endocytosis of CD80 efficiently promotes PD-L1 availability.